Cultural evaluation and flood management recommendation for local settlement in mitigating flood disaster in Kelantan River Basin, Malaysia - Daud, Muhammad Lutfi (2018)
Recent huge flood on last December 2014 that affected east-coast of Malaysia, especially Kelantan has disrupted and caused big damages to the local community physically and mentally. The 2014 flood is believed as the largest and uncontrollable recorded flood in the history of Kelantan. Thus, this research is being conducted in order to identify lifestyle changes experienced by Kelantan community during before and after the enormous flood event. The study intends to compare existing flood procedure with other countries before proposing the new settlement aid based on the cultural analysis and consideration. In order to conduct the research, this study has done content analysis and evaluated opinions from previous researchers regarding the flood incidents in Malaysia focusing the events in Kelantan. Qualitative interview has been constructed and done with the experts and professionals whom directly involve in mitigating the flood disaster in last 2014. They have been helping in validating the data collected from the site visit. The research results are able to show the lifestyle changes before and after the flood among the locals and a proper cultural framework of Kelantan community will be constructed. Later, the framework will be beneficial in mitigating the flood disaster especially in term of settlement aids. This is important in order to understand the effect of disaster upon culture of a community, which directly able to increase the preparedness of that particular community to face the upcoming disaster again.